An intertextual reading of contemporary Zimbabwean poetry with particular attention to the anthology, State of the Nation - Chivhere, Tinashe Fortune (Midlands State University, 2014)
Intertextuality is the presence of a text in other texts, intertextuality can be something that a reader identifies when reading a text or it can be deliberate connections that a writer makes to other existing texts. The objective of the study is to analyse the anthology, State of the Nation and find out if the poets made any reference to already existing works as well as find out if the reader can make connections to already existing literary works